2022
DOI: 10.1101/2022.11.04.515212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opi1-mediated transcriptional modulation orchestrates genotoxic stress response in budding yeast

Abstract: Inositol is a six-carbon sugar that functions as a precursor for signaling molecules such as phosphoinositides and inositol polyphosphates, which are involved in the regulation of important biological processes such as energy metabolism, environmental stress response, phosphate signaling, among others. Given its role in a myriad of signaling pathways, regulation of inositol synthesis is essential for cellular homeostasis. In budding yeast, transcription of genes involved in inositol metabolism is regulated by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…The study's line of reasoning was validated by a genetic rescue experiment, wherein the deletion of KCS1 in an opi1∆ knockout strain successfully mitigated the MMS sensitivity that typically manifests in the absence of Opi1. This outcome implies a contrasting function for Opi1 and PP-IPs in the modulation of Ino2-Ino4 action [47].…”
Section: Genotoxic Stressmentioning
confidence: 93%
See 1 more Smart Citation
“…The study's line of reasoning was validated by a genetic rescue experiment, wherein the deletion of KCS1 in an opi1∆ knockout strain successfully mitigated the MMS sensitivity that typically manifests in the absence of Opi1. This outcome implies a contrasting function for Opi1 and PP-IPs in the modulation of Ino2-Ino4 action [47].…”
Section: Genotoxic Stressmentioning
confidence: 93%
“…The focal point of this argument is Opi1, studied for its potential to mediate genotoxic stress. A recent study [47] revealed that in opi1∆, the expression of INO1, involved in the synthesis of inositol phospholipids and inositol polyphosphates, exhibited a significant increase upon exposure to the genotoxic agent methyl methane sulfonate (MMS). This induction of INO1 expression is attributed to the activation mediated by Ino2-Ino4 [48], transcriptional activators whose levels surge in the absence of Opi1.…”
Section: Genotoxic Stressmentioning
confidence: 99%